Effect of acetogenin fraction of Annona muricata leaves on antioxidant status and some indices of benign prostatic hyperplasia in rats - Patience N. Ogbu; Evelyn O. Ugota; Rita U. Onwuka; Ikechukwu M. Ogbu; Chinyere Aloke (Taylor & Francis Group, 2020)
Objectives: This work investigated the effect of acetogenin-rich fraction of Annona muricata leaves (AFAL) on antioxidant status and some markers of benign prostatic hyperplasia (BPH) in rats. Methods: BPH was experimentally induced in the rats by subcutaneous injection of testosterone propionate (TP, 3 mg/kg) for 28 consecutive days. The rats were administered orally different doses of AFAL (100 and 200 mg/kg) for 7 days. Prostate-specific antigen (PSA), prostate weight, relative prostate weight, prostate protein content and oxidative stress indices of the rats were evaluated. Results: It was observed that 200 mg/kg AFAL significantly reduced the PSA level, mean prostate weights and mean relative prostate weights of the test rats compared to the TP group, and the values were not significantly different from the normal control and group treated with a standard drug. The plant extract also significantly enhanced the antioxidant capacity of the test rats which were evidently compromised in the group that received the exogenous hormone alone. Histopathology of the prostate showed a marked recovery for the test rats after treatment with AFAL. Conclusion: Oral administration of acetogenin-rich fraction of Annona muricata leaves ameliorated TP-induced BPH in rats and significantly enhanced the antioxidant capacity of the rats.